Participatory exploration of the heterogeneity in household socioeconomic, food and nutrition security status for the identification of nutrition-sensitive interventions in the Rwandan Highlands - Mashingaidze, N.; Ekesa, B.; Ndayisaba, C.P.; Njukwe, E.; Groot, Jeroen C.J.; Gwazane, M.; Vanlauwe, Bernard (Frontiers Media, 2020)
Food insecurity and malnutrition are challenges in rural Rwanda that are presumed to be affected by differential household socioeconomic status, but the relationship between food and nutrition security and socioeconomic status is not well-understood. We used a participatory and multidisciplinary study comprising nutrition survey, focus group discussion (FGD), detailed household/farm characterization, and interviews to construct a participatory household typology and to determine differences in the socioeconomic, food, and nutrition security status of 17 households representing the identified household types in Nyabihu District of Western Province. Strategies to improve household food and nutrition security were identified by the case study households themselves. During the FGDs, it was hypothesized that financial, physical, and natural capitals varied, resulting in high, medium, and low resource endowed households, abbreviated as HRE, MRE, and LRE, respectively. The HRE households had the most educated household heads, largest landholdings (~1 ha), and highest agricultural biodiversity and total farm income per annum. This probably resulted in better diets for women, children higher household food consumption relative to the other households. In contrast, the LRE households were the least food-secure, with poor household food consumption and low dietary diversity across seasons, probably due to limited physical and economic access to food. However, anthropometry of women and children did not differ with household type. Half of the children were stunted, including some from the more food-secure HRE households. Undiversified, nutritionally inadequate diets and bouts of illness likely contributed to chronic malnutrition in children. Making agricultural programs more nutrition-sensitive, creating diverse employment opportunities, and sensitizing communities to nutrition and adequate feeding practices of children could complement the interventions identified by households to improve their food and nutrition security.